Effect of storage time on mirror carp (Cyprinus carpio L.) pastrami stored in market temperature - Arslan, Ali; Gönülalan, Zafer; Çelik, Cernai (Scientific and Technical Research Council of Turkey, 1997)
the aim of this study was to determination of microbilogical and chemical properties and effect of vacuum during storage period of vacuumed and unvacuumed Mirror carp (Cyrinus carpio L.) pastrami. Pastrami samples produced experimentally and stored in market (20°C) conditions. 0, 7, 14, 21, 30, 45, 60, 90 and 120th days of maturity analysis were performed. Unvacuumed pastrami samples analysis had been until 45th day of maturiyt due to lose high amount of moisture. In microbiologic analysis number of bacteria were decreased during storage period. In vacuumed pastrami samples numbers of viable aerobes, anaerob microorganisms, psychrophiles, lactobacillus, Staphylococcus - Micrococcus, yeast and molds were between 1.8 × 104 - 9.1 × 105 cfu/g: 7.4 × 103 - 7.1 105 cfu/g; 0 - 3.6 × 102 cfu/g: 6.6 × 10 - 1.4 × 104 cfu/g: 6.5 103 - 1.5 × 105 cfu/g: 0 - 2.3 × 102 cfu/g and in unvacuumed pastrami were between 1.5 × 103 - 8.9 × 105 cfu/g; 7.1 × 102 - 3.6 × 105 cfu/g: 0 - 9.6 × 10 cfu/g: 9.5 × 10 - 1.3 103 cfu/g: 2.3 × 102 - 6.0 × 104 cfu/g; 0 - 4.0 × 10 cfu/g; respectively. Coliforms were not noticed in both vacuumed and unvacuumed pastrami samples. Differencies in viable aerobes on 14, 21, 45th days, in anaerob microorgainsms and Staphylococcus - Micrococcus on 30, 45th. in Lactobacillus on 45th, in yeasts and molds first and 14th days of maturity were significant between pastrami samples (p<0.05). During the storage period pH levels were decreased in vacuumed and unvacuumed pastrami samples. Moisture content were decreased in unvacuumed pastrami samples. Moisture, fat, ash, salt and pH values in vacuumed pastrami samples were between 32.48 - 36.81%; 6.33 - 8.42%; 9.75 - 11.94%; 8.33 - 12.91%; 5.41 - 5.92 and in unvacuumed pastrami same values were between 15.96 - 38.13%; 7.77 - 14.88%; 5.51 - 15.60%; 7.75 - 14.68%; 5.65 - 5.96 respectively. Statistically, the differencies between both vacuumed and unvacuumed pastrami samples for moisture on 7, 14, 21, 30 and 45th, for fat content on 7, 30 and 45th days of maturity, for salt content first and 30th days, for ash content during the storage period were significant (p<0.05). In conclusion microbiologic and chemical results indicated that vacuumed mirror carp pastrami samples keeps quality characteristics at least 120 days of storage in market temperature.
Market sicakli?inda muhafaza edilen aynali sazan (Cyprinus carpio L.) pastirmalarinda muhafaza süresinin etkisi
Keywords: Chemical; Fish; Microbiologic; Pastrami; Quality; Temperature